2017
DOI: 10.1101/gad.292169.116
|View full text |Cite
|
Sign up to set email alerts
|

Cbx3 maintains lineage specificity during neural differentiation

Abstract: Chromobox homolog 3 (Cbx3/heterochromatin protein 1γ [HP1γ]) stimulates cell differentiation, but its mechanism is unknown. We found that Cbx3 binds to gene promoters upon differentiation of murine embryonic stem cells (ESCs) to neural progenitor cells (NPCs) and recruits the Mediator subunit Med26. RNAi knockdown of either Cbx3 or Med26 inhibits neural differentiation while up-regulating genes involved in mesodermal lineage decisions. Thus, Cbx3 and Med26 together ensure the fidelity of lineage specification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 40 publications
(46 reference statements)
4
36
1
Order By: Relevance
“…4j-k, left). We also evaluated the RNA expression levels of genes co-marked with H4K20me3/H3K4me3 relative to H4K20me3, H3K9me3, or H3K4me3 regions in MEFs (see methods) and NPs (GSE89574) [28]. Our findings demonstrate that genes co-marked by H4K20me3/ H3K4me3 in ES cells is significantly lower relative to genes marked by H3K4me3 (Fig.…”
Section: H4k20me3/h3k4me3 Marks Transcriptionally Dynamic Genes In Esmentioning
confidence: 83%
See 1 more Smart Citation
“…4j-k, left). We also evaluated the RNA expression levels of genes co-marked with H4K20me3/H3K4me3 relative to H4K20me3, H3K9me3, or H3K4me3 regions in MEFs (see methods) and NPs (GSE89574) [28]. Our findings demonstrate that genes co-marked by H4K20me3/ H3K4me3 in ES cells is significantly lower relative to genes marked by H3K4me3 (Fig.…”
Section: H4k20me3/h3k4me3 Marks Transcriptionally Dynamic Genes In Esmentioning
confidence: 83%
“…k Empirical cumulative distribution function (ECDF) for RNAPII density in mouse fibroblasts (left) and neural progenitors deactivation of RNAPII binding upon downregulation of OCT4. Likewise, to investigate whether H4K20me3/ H3K4me3 poises genes for deactivation of RNAPII binding during lineage-specific differentiation, we evaluated RNAPII binding using public ChIP-Seq data from mouse fibroblasts (MEFs) (GSE71507) and neural progenitor cells (NP) (GSE89573) [28]. Results from these analyses demonstrate that RNAPII binding was significantly lower at H4K20me3/H3K4me3 regions relative to H3K4me3 regions ( Fig.…”
Section: H4k20me3/h3k4me3 Marks Transcriptionally Dynamic Genes In Esmentioning
confidence: 99%
“…5A). Recent studies have shown that some repressive chromatin modifiers regulate lineage fidelity during neural differentiation of ESCs by enhancing neural gene expression and suppressing genes specific to other lineages (8,9). Furthermore, a previous report has shown that the CHD4/NuRD complex establishes the identities of the two striated muscle types, cardiac and skeletal muscle, by suppressing the alternate lineage gene program (34).…”
Section: Inhibition Of Mesendoderm Differentiation Does Not Affect Immentioning
confidence: 99%
“…Previous studies have uncovered that the intrinsic programs mediated by transcription factors and epigenetic regulators play important roles in the default model of neural fate determination (3)(4)(5)(6)(7). Recent studies have shown that repressive chromatin modifiers, polycomb repressive complex 2 (PRC2) and Chromobox homolog 3, regulate lineage fidelity during neural differentiation of ESCs by enhancing neural gene expression and suppressing the genes specific to other cell lineages (8,9). These results indicate the importance of repressive chromatin modifiers in neural lineage commitment.…”
mentioning
confidence: 98%
“…Beyond their role in structuring heterochromatin, HP1 proteins also functions as regulators of euchromatic transcription. For instance, at the promoters of many inducible genes involved in development or in cellular defense, they participate in the transient silencing of transcription while awaiting stimulation [15][16][17][18][19][20] . But HP1 proteins, in particular HP1g in mammals, are also present inside the coding region of genes 21 , a localization which is not always correlated with H3K9me3 19 .…”
Section: Introductionmentioning
confidence: 99%